The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1053/j.gastro.2016.06.045
|View full text |Cite
|
Sign up to set email alerts
|

A Frameshift in CSF2RB Predominant Among Ashkenazi Jews Increases Risk for Crohn's Disease and Reduces Monocyte Signaling via GM-CSF

Abstract: Background & Aims Crohn’s disease (CD) has the highest prevalence in Ashkenazi Jewish populations. We sought to identify rare, CD-associated frameshift variants of high functional and statistical effects. Methods We performed exome-sequencing and array-based genotype analyses of 1477 Ashkenazi Jewish individuals with CD and 2614 Ashkenazi Jewish individuals without CD (controls). To validate our findings, we performed genotype analyses of an additional 1515 CD cases and 7052 controls for frameshift mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…1 A rare dominant negative frameshift mutation in the GM-CSF receptor beta chain gene CSF2RB reduces GM-CSF activation of STAT5 in monocytes and increases risk for adult-onset CD. 9,10 We discovered that common neutralizing GMAb, which inhibit GM-CSF signaling in a cell-extrinsic manner, are associated with reduced neutrophil bacterial killing and higher rates of stricturing complications in pediatric and adult-onset CD. 4,5 In the current study, we have identified a subset of pediatric CD patients characterized by low/normal neutrophil-intrinsic GMSI, which was in turn associated with a CSF2RA A17G missense mutation, alterations in wound healing and cell survival gene programs, and high rates of disease complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A rare dominant negative frameshift mutation in the GM-CSF receptor beta chain gene CSF2RB reduces GM-CSF activation of STAT5 in monocytes and increases risk for adult-onset CD. 9,10 We discovered that common neutralizing GMAb, which inhibit GM-CSF signaling in a cell-extrinsic manner, are associated with reduced neutrophil bacterial killing and higher rates of stricturing complications in pediatric and adult-onset CD. 4,5 In the current study, we have identified a subset of pediatric CD patients characterized by low/normal neutrophil-intrinsic GMSI, which was in turn associated with a CSF2RA A17G missense mutation, alterations in wound healing and cell survival gene programs, and high rates of disease complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 We therefore asked whether differences in neutrophil bacterial killing with GMSI would be specific to the GM-CSF:STAT5 pathway or if they reflect a broader dysregulation of cell signaling networks. 9 We conducted an unbiased survey of 10 key cell signaling phospho-protein targets under steady-state conditions. Although we did not observe significant differences in phospho-protein abundance that survived corrections for multiple comparisons, we did observe nominal increases in STAT1 and NFkB activation in the GMSI-Hi neutrophils, which were supported by the gene expression data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our finding, we predict that while the genetic landscape of the second-generation immigrants will be similar to their parents, the genetic correlation to Paneth cell defects will trend more toward European ancestry North American CD. In addition, conducting genetic-Paneth cell defect analysis with focused ethnic groups (e.g., Ashkenazi Jewish) (61,62) and with cross-ethnic groups (5) may provide additional insight into potential gene-gene interactions in triggering Paneth cell defect.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…They identified a frameshift mutation in CSF2RB as a strong causal candidate which was associated with CD at p<3.5×10 -6 and an OR of 1.5 369 . This variant is rare in the non-AJ population.…”
Section: Other Investigations To Identify Causal Moleculesmentioning
confidence: 99%